Who has Their Finger on the Pulse of Power and Potential? An Exploration of AI Systems in Arc of a Scythe and the Powers that Bind Them - Christiansen, Annemarie (Trinity College Dublin, School of Languages, Literatures, and Cultural Studies, Digital Humanities and Culture, 2025)
As artificial intelligence is deployed within every aspect of everyday life, academics and ordinary people are grappling with how this will shape the future as a result of social and cultural expectations. Neal Shusterman’s Arc of a Scythe (2016-2022) is a Young Adult Science Fiction novel series that explores the intersec4on between technology, society, culture, and the future through its characteriza4on of a conscious artificial intelligence system in control of the en4re world. By applying Jasanoff and Kim’s (2015) theoretical framework of sociotechnical imaginaries to the texts, the imaginary that characterizes the artificial intelligence is brought to light as a manifesta4on of what future systems could look like while allowing its readership the space to apply their own experience and draw their own conclusions. This dissertation divides the system into three categories of technological system, governmental body, and a God to sufficiently outline and highlight the imaginary itself, as well as the power hierarchies that grant the system the authority and influence it has cultivated and maintained. These sociocultural ins4tu4ons provide strength and power not only within the series but in reality, as readers draw on their own knowledge and perspectives to fully render the artificial intelligence system and investigate their position towards it. This dissertation takes the position that the artificial intelligence system acts as a sociotechnical imaginary that exposes the power hierarchies derived from institutions in reality to expose a potential future run by artificial intelligence and the readers’ response to that.